ETOS PENDIDIKAN DAN KESEJAHTERAAN MIGRAN MUSLIM STUDI KASUS DI PEMUKIMAN MIGRAN PANGKOH KAB. PULANG PISAU PROVINSI KALIMANTAN TENGAH - Qodir, Abdul (PSIKOPEDAGOGIA Jurnal Bimbingan dan Konseling, 2012)
Muslim migrants in society Pangkoh much success in the field of education, work, and life is better in the third decade (2002-2011). In fact, at the beginning of the decade arrived I (1982-1991), a small portion has a secondary education, the majority of elementary school, all start a new life. MasaIahnya ethos is focused on education and welfare. This research is descriptive qualitative, which is closely related to cultural studies. The approach used in this study is ethnography in an effort to understand the ethos of education and prosper in migrant communities Pangkoh. Subjects were Pangkoh Muslim migrants. In collecting the data, using primary techniques are in-depth interviews and observations hooks with problems. The data were analyzed qualitatively ie by way of narrative and interpretive description of the phenomenon and welfare ethos that has been found in the Muslim migrant families studied. This study shows that, first, the Muslim migrant communities in the early arriving (1982) educated middle or slightly higher in the second decade increased by taking up a bachelor S.1 for himself and family. The principal work of this group some Muslim migrants increased in rank and the task of leading the school. Increased revenue from the allowances and benefits lead educator certification. Second, Muslim migrant communities that early arrival basic education, primary school or its equivalent, has the educational ethos that indirectly, in three decades.